2015
DOI: 10.1002/eat.22437
|View full text |Cite
|
Sign up to set email alerts
|

Medical outcomes for adults hospitalized with severe anorexia nervosa: An analysis by age group

Abstract: Results demonstrate medical abnormalities and response to medical stabilization in severely ill AN patients during hospitalization were mostly similar across the age span. This information should allay fears that the effect of age will make medical stabilization more difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…Despite the few comparators, we found that key demographics of our population were largely concordant with other centres. [13][14][15][16][17] In addition, the high frequency of comorbid psychiatric illness in our cohort was consistent with data from Buhren et al, 18 who described comorbid illness in 47.3% of patients with first presentation AN, and Fichter et al, 19 who reported comorbid Axis I disease in 76.6% of 103 prospectively recruited AN inpatients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Despite the few comparators, we found that key demographics of our population were largely concordant with other centres. [13][14][15][16][17] In addition, the high frequency of comorbid psychiatric illness in our cohort was consistent with data from Buhren et al, 18 who described comorbid illness in 47.3% of patients with first presentation AN, and Fichter et al, 19 who reported comorbid Axis I disease in 76.6% of 103 prospectively recruited AN inpatients.…”
Section: Discussionsupporting
confidence: 91%
“…[13][14][15][16][17] In addition, the high frequency of comorbid psychiatric illness in our cohort was consistent with data from Buhren et al, 18 who described comorbid illness in 47.3% of patients with first presentation AN, and Fichter et al, 19 who reported comorbid Axis I disease in 76.6% of 103 prospectively recruited AN inpatients. [13][14][15][16][17] In addition, the high frequency of comorbid psychiatric illness in our cohort was consistent with data from Buhren et al, 18 who described comorbid illness in 47.3% of patients with first presentation AN, and Fichter et al, 19 who reported comorbid Axis I disease in 76.6% of 103 prospectively recruited AN inpatients.…”
Section: Inpatient Management Of Anorexia Nervosasupporting
confidence: 91%
See 2 more Smart Citations
“…One should keep in mind though, while interpreting the results of our study, that a diagnosis of AN did neither require that AN was the leading current diagnosis nor that it was the first episode of AN. Second, current research has highlighted the occurrence of AN in mid-life and older adults [32,33,49]. Third, studies in AN have used different upper age limits, for example, 40 years of age [20,31], even though other studies have shown that in a relevant proportion of people with AN is first diagnosed or first treated after the age of 40 [32,33].…”
Section: Comparison To Previous Researchmentioning
confidence: 99%